1991
DOI: 10.1002/prot.340090302
|View full text |Cite
|
Sign up to set email alerts
|

A metal‐mediated hydride shift mechanism for xylose isomerase based on the 1.6 Å Streptomycs rubiginosus structure with xylitol and D‐xylose

Abstract: The crystal structure of recombinant Streptomyces rubiginosus D-xylose isomerase (D-xylose keto-isomerase, EC 5.3.1.5) solved by the multiple isomorphous replacement technique has been refined to R = 0.16 at 1.64 A resolution. As observed in an earlier study at 4.0 A (Carrell et al., J. Biol. Chem. 259: 3230-3236, 1984), xylose isomerase is a tetramer composed of four identical subunits. The monomer consists of an eight-stranded parallel beta-barrel surrounded by eight helices with an extended C-terminal tail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
282
0
2

Year Published

1994
1994
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(309 citation statements)
references
References 55 publications
25
282
0
2
Order By: Relevance
“…In xylose isomerase, such an exchange is prevented in part by a tryptophan residue (Trp-16), which forms a hydrophobic envelope around the site of hydrogen transfer (7). Similarly, in the complex of PfPGI with 6PG, the tetrahedral density at the C2 position of the inhibitor indicates that the transferred hydrogen projects in toward the active site where it is framed by a markedly hydrophobic region.…”
Section: Discussionmentioning
confidence: 99%
“…In xylose isomerase, such an exchange is prevented in part by a tryptophan residue (Trp-16), which forms a hydrophobic envelope around the site of hydrogen transfer (7). Similarly, in the complex of PfPGI with 6PG, the tetrahedral density at the C2 position of the inhibitor indicates that the transferred hydrogen projects in toward the active site where it is framed by a markedly hydrophobic region.…”
Section: Discussionmentioning
confidence: 99%
“…In XYL, Lys-182 makes a hydrogen bond to O1 of the ligand. Another interesting similarity between XYL and PGI is that both enzymes have been proposed to use a histidine residue to catalyze ring-opening of the bound cyclic substrates (64) and thereafter this histidine interacts with the hydroxyl on C5 of the linear substrate. However, it should be noted that later studies of XYL challenged the involvement of a histidine in the ring-opening step (65,66).…”
Section: Comparison Of Pgi͞5pah To Complexes Of Tim and Xyl With Analmentioning
confidence: 99%
“…However, it should be noted that later studies of XYL challenged the involvement of a histidine in the ring-opening step (65,66). It was also reported that the XYL active site base that transfers the proton between O1 and O2 is assumed to be a hydroxide ion ligated to one of the metal ions (64,67). This situation is analogous to what we propose to occur in PGI, for which lowering of the pKa of water423 would not be achieved by a metal ion, but by the surrounding network of water molecules.…”
Section: Comparison Of Pgi͞5pah To Complexes Of Tim and Xyl With Analmentioning
confidence: 99%
“…A number of laboratories have studied the structure of GI isolated from different bacterial species by X-ray crystallography, with or without inhibitors or metal ions present, in order to understand and explain its mechanism of activity: XI, Actinoplanes missouriensis, 2.8 A resolution (Rey et al, 1988); XI, Streptomyces olivochromogenes, 3.0 A resolution (Farber, Glasfeld, Tiraby, Ringe & Petsko, 1989); XI, Arthrobacter, 2.5/k resolution (Henrick, Collyer & Blow, 1989); XI, Streptomyces rubiginosis, 1.9 A resolution (Carrell et al, 1989;Collyer, Henrick & Blow, 1990); XI, Streptomyces albus, 1.65 A resolu-© 1994 International Union of Crystallography Printed in Great Britain -all rights reserved tion (Dauter, Terry, Witzel & Wilson, 1990); XI, Streptomyces rubiginosus, 1.6 A resolution (Whitlow et al, 1991). The mechanism has been suggested to involve a metal-mediated 1,2 hydride shift (Collyer, Henrick & Blow, 1990, Whitlow et al, 1991.…”
Section: Introductionmentioning
confidence: 99%